Targeting RANKL in the management of bone loss in patient with breast cancer - Nicolin, Vanessa; Valentini, Roberto (Italian Journal of Anatomy and Embryology, 2014)
The receptor activator of nuclear factor-κB ligand (RANKL), its signaling receptor RANK, and its natural decoy receptor OPG are members of the tumour necrosis factor (TNF) and TNF receptor superfamily and are best known for their essential role in controlling osteoclastogenesis. RANKL in bone has also been shown to serve as a chemoattractant for cancer cells, thus explaining the tropism of certain cancers such as breast and prostate cancer to preferentially metastasize to bone. Here, we will discuss the important role of RANKL and its possible role in the management of bone loss in patients with breast cancer.